Методологія визначення критеріїв прогнозування та комплексної оцінки вуглеводневих покладів різних типів - Кришталь, А.М. (Геоінформатика, 2015)
Розглянуто загальні, необхідні та достатні критерії для прогнозування та оцінки традиційних вуглеводневих джерел, а також пошуково-прогнозні критерії для вуглеводневих покладів нетрадиційних типів. Передбачається можливість сингенетичності геологічних умов формування вуглеводнів різних видів з потенційними ресурсами, які у багато разів перевищують загальну оцінку традиційних ресурсів. Найважливішим із необхідних критеріїв утворення джерел вуглеводнів у Дніпровсько-Донецькій западині є відносна стабільність нафтогазогеологічних умов і процесів, яка впливає на їх масштабність. Окреслено основні завдання для розв’язання проблеми комплексного виявлення та освоєння вуглеводневих джерел України. Рассмотрены общие, необходимые и достаточные критерии для прогнозирования и оценки традиционных углеводородных источников, а также поисково-прогнозные критерии для углеводородных залежей нетрадиционных типов. Предусматривается возможность сингенетичности геологических условий формирования углеводородов различных видов с потенциальными ресурсами, которые во много раз превышают общую оценку традиционных ресурсов. Важнейшим из необходимых критерием образования источников углеводородов в Днепровско-Донецкой впадине является относительная стабильность нефтегазогеологических условий и процессов, которая влияет на их масштабность. Описаны основные задачи для решения проблемы комплексного выявления и освоения углеводородных источников Украины. Purpose. To provide Ukraine with its own energy sources, there must be effective means and ways of replenishing its hydrocarbon resource basis. Addressing those objectives requires highly robust geological prognosis for developing geotechnological projects of comprehensive and complex utilization of a broad section of litho-stratigraphy to technically allowable depths, creating reliable geological models, and improving oil and gas wells testing and exploitation techniques. Design/methodology/approach. Enhancements of common, necessary and satisfactory criteria for prognosis and evaluation of hydrocarbon reservoirs of conventional types, as well as the development of exploration prognosis criteria for unconventional resources of hydrocarbons (shale/tight gas, CBM, tight sandstones, central-basin type gas reservoirs) were carried out based on the results of analysis of oil and gas geology researches of different local and foreign sources.
Findings. The main important criterion of the hydrocarbon reservoirs formation in the Dnepr-Donetsk depression is determined as a relative stability of petroleum geology conditions and processes that affect their continuity.
Allowance is made for possibility of syngenetic of geological conditions for generating hydrocarbon reservoirs of different types.
Practical value/implications. We identified the main objectives in solving the problem of complex prognosis, exploration and development of the hydrocarbon resource basis.